Simulation and Fault Diagnosis Using Current-Voltage Characteristics of Photovoltaic Systems—A Case Study - Jhih-Hao Lin; Yuan-Kang Wu (Engineering Proceedings)
The I-V characteristics of a photovoltaic (PV) system reveal its actual state and performance, and are used for fault detection and diagnosis in PV systems. We reviewed modeling methods for common faults using MATLAB/Simulink R2021a software, including module degradation, open-circuit faults, short-circuit faults, shading faults, and hotspot faults, in this study. A detailed analysis was conducted regarding how these faults impact I-V characteristics. Taking a real PV system as an example, a fault diagnosis case study was carried out. By fitting the measured I-V curves from the PV system and diagnosing potential faults and their severity based on the fitted model parameters, the approach proposed in this study offers a cost-free, simple, and effective detection method. This method can be used by researchers and engineers in the PV field for the advanced fault detection and diagnosis of PV systems.